High Altitude Polycythemia Presenting as Atypical Chest Pain with TMT Positive and Normal Coronaries - Anand, DR N N; TM, DR Karthikeya; Sriramulu, DR Divya (South Eastern European Journal of Public Health, 2024)
High-altitude polycythemia (HAP), also known as chronic mountain sickness (CMS), is a condition in which individuals residing at high altitudes develop increased red blood cell mass in response to chronic hypoxia. This leads to increased hemoglobin and hematocrit levels, which can result in complications such as blood hyperviscosity, thrombotic events, and rarely, cardiovascular symptoms like chest pain. This case report illustrates a patient presenting with atypical chest pain, a positive treadmill test (TMT), and normal coronary angiography, whose symptoms were ultimately attributed to HAP.